PEMANFAATAN E-TOURISM UNTUK PEMASARAN SEKTOR PARIWISATA DI KOTA MAKASSAR BERBASIS ANDROID - Methodius Dickyar F. Junaidy J.; Hamdan Arfandy; Syamsul Bahri (STMIK KHARISMA Makassar, 2020)
This research aims to design the utilization of E-tourism for the marketing of tourism sector in Makassar based on Android. The function of this research is to facilitate the Investor who want to find tourist sites and tourist attractions that want to buy or develop and other functions of the research is to facilitate the user to provide information to the Investor both institutions and individuals who want to develop or buy tourist attractions in the direction of data collection by studying materials, concepts, books and theories relating to the drafting process and the discussion of issues discussed by the authors included in the literature on authors and About things that support the creation of application programs. The author has managed to make application of E-Tourism utilization for tourism sector marketing in the city of Makassar based on Android. Application design process using Android platform using Android Studio software. Evaluation results from BlackBox testing to determine the reliability of the application shows that all results are valid or as expected.